Light touch - Leather, Stephen (Leather, Stephen. Spider Shepherd, 2017)
Working undercover is all about trust - getting the target to trust you and then betraying them in order to bring them to justice. But what do you do when you believe an undercover cop has crossed the line and aligned herself with the international drugs smuggler she was supposed to be targeting? When a deep-undercover cop stops passing on intelligence about her target, MI5 sends in Dan 'Spider' Shepherd to check that she is on the straight and narrow. Now two lives are on the line - and Shepherd discovers that the real danger is closer to home than he realised. As Spider finds his loyalties being tested to the limit, an SAS killer is on a revenge mission in London and only Spider can stop him.